2019
DOI: 10.5604/01.3001.0013.6189
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Influence of Distance Between Cars on the Driver Psychophysiology During Braking Using Eeg: A Case Study on Driving in Indonesia

Abstract: The multiple crashes in Indonesia are categorized into a frequently occurring accident, which often causes death. The aim of this paper is to examine the driver psychophysiology during braking in response to the vehicle in the front, which is varied. The research was initiated with a literature review regarding the electrooculography (EEG), safe braking distance, Emotive Epoc+, and Central Nervous System (CNS). The research was initiated with a literature review regarding the Electroencephalography (EEG), saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The assertion that braking as a response to a STOP sign elicits stress has a vast support (e.g., Min et al, 2002;Collet et al, 2014;Prasolenko et al, 2017;Sugiono et al, 2019). Accordingly, the LMM analyses conducted in the current study revealed that, during braking as a response to a STOP sign, maximal deceleration had a highly significant effect on the HR measure.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The assertion that braking as a response to a STOP sign elicits stress has a vast support (e.g., Min et al, 2002;Collet et al, 2014;Prasolenko et al, 2017;Sugiono et al, 2019). Accordingly, the LMM analyses conducted in the current study revealed that, during braking as a response to a STOP sign, maximal deceleration had a highly significant effect on the HR measure.…”
Section: Discussionsupporting
confidence: 50%
“…Such changes may result from the road conditions and unexpected factors that force emergency maneuvers (i.e., a braking sign or a figure bursting into the road). Specifically, stopping in response to a STOP sign during driving and the necessity to brake have been found to induce stress in an experimental context ( Min et al, 2002 ; Collet et al, 2014 ; Prasolenko et al, 2017 ; Sugiono et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%